2011
DOI: 10.1007/s11064-011-0636-6
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-Rb Mediating Cell Cycle Reentry Induces Early Apoptosis Following Oxygen–Glucose Deprivation in Rat Cortical Neurons

Abstract: The aim of this study was to investigate the relationship between cell cycle reentry and apoptosis in cultured cortical neurons following oxygen-glucose deprivation (OGD). We found that the percentage of neurons with BrdU uptake, TUNEL staining, and colocalized BrdU uptake and TUNEL staining was increased relative to control 6, 12 and 24 h after 1 h of OGD. The number of neurons with colocalized BrdU and TUNEL staining was decreased relative to the number of TUNEL-positive neurons at 24 h. The expression of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…In addition to the increase in the NSC death, we also found more apoptotic neuroblasts and neurons, represented by AC3 + DCX + cells and AC3 + Tuj1 + cells at 15 and 28 DIV, respectively. Similar results were previously observed in mice (Yu et al, 2012;Vandenbosch et al, 2016). In addition, there was no significant change in S-phase entry in RB1-KO organoids compared with wild type at 15 DIV, which is in line with no difference in organoid size between wild type and RB1-KO at this stage.…”
Section: Role Of Rb In Cell Proliferation and Cell Deathsupporting
confidence: 90%
See 4 more Smart Citations
“…In addition to the increase in the NSC death, we also found more apoptotic neuroblasts and neurons, represented by AC3 + DCX + cells and AC3 + Tuj1 + cells at 15 and 28 DIV, respectively. Similar results were previously observed in mice (Yu et al, 2012;Vandenbosch et al, 2016). In addition, there was no significant change in S-phase entry in RB1-KO organoids compared with wild type at 15 DIV, which is in line with no difference in organoid size between wild type and RB1-KO at this stage.…”
Section: Role Of Rb In Cell Proliferation and Cell Deathsupporting
confidence: 90%
“…What is surprising is that there was also increased cell death in RB1-KO organoids compared with wild type at 28 DIV, possibly due to an increase of the proapoptotic gene BAX (Drew et al, 2016). In line with our results, it has been described that loss of RB in mice promotes apoptosis in the developing and adult brain (Macleod et al, 1996;Vandenbosch et al, 2016;Yu et al, 2012). However, other studies have shown that an increase in cell proliferation due to the lack of RB is not followed by enhanced cell death (MacPherson et al, 2003).…”
Section: Role Of Rb In Cell Proliferation and Cell Deathsupporting
confidence: 87%
See 3 more Smart Citations